ANALISIS PENGARUH PAJAK HOTEL DAN RESTORAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA PEMERINTAH KOTA BANDUNG - Arini, Sulistyo; Astutik, Erni Puji (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Hotel taxes and restaurant taxes are two types of local taxes, and the potential to encourage regional development is growing as policies increasingly pay attention to supporting elements such as the service industry, development and tourism. The purpose of this study was to determine the effect of hotel and restaurant taxes on local revenue in the city of Bandung. Qualitative research methods are descriptive and aim to enable researchers to describe research in a systematic, detailed, and in-depth manner and uncover the implications of facts. Data collection techniques were carried out through observation of the financial reporting website of the Regional Taxation Agency (BAPENDA) Bandung City. The partial test results show that the hotel tax has no partial effect on Bandung City Original Revenue. While the test results partially affect the restaurant tax, the restaurant tax partially affects the local revenue of the city of Bandung. Therefore, both hotel tax and restaurant tax have an impact on Bandung City's original income at the same time.